Fostering Entrepreneurial Readiness through Education: The Impact of Motivation, Competence, and Creativity Development in Higher Education - Fresa Dwi Juniar; Ani Sulistiani Faizah (Indonesian Journal of Business and Entrepreneurship Research, 2025)
Unemployment remains one of the major challenges in Indonesia, largely due to the country's high population growth rate, which intensifies competition in securing employment. One of the most effective solutions to address this issue is by increasing the number of entrepreneurs. This study aims to examine the direct and indirect effects of motivation, competence, creativity, and entrepreneurship education on students' entrepreneurial readiness. A quantitative approach with a descriptive explanatory design was adopted, involving a population of 492 students. A sample of 103 students from the Faculty of Economics at Universitas Negeri Makassar was selected using proportional random sampling. The findings indicate that motivation, competence, student creativity, and entrepreneurship education significantly influence entrepreneurial readiness, both directly and indirectly. These results suggest that entrepreneurship education programs should emphasize not only product development but also marketing, decision-making, and business evaluation skills. The study provides valuable insights for educators to better guide students in enhancing their entrepreneurial capabilities. Future research is encouraged to broaden the scope of variables and apply more diverse methodological approaches to deepen understanding in this area.